Pengaruh Efektivitas Pelatihan Daring Terhadap Kinerja Di PT Kalbe Milko Indonesia - Hartanto; Don Gusti Rao; Salma Athiyyah Fajri (MAMEN: Jurnal Manajemen, 2022)
Training is very necessary to increase the capacity and competence of employees. The implementation can be done face-to-face (offline) or remotely (online). Currently, online training methods are needed to overcome the problems of implementing training due to the Covid 19 pandemic which limits meetings within a company. The effectiveness of the results of the online training can be measured through employee performance appraisals. The purpose of this study is to find out how the effectiveness of online training has on employee performance. The study used a quantitative approach with data collection techniques through questionnaires. Using a sample of 106 employees of the Production Department of PT Kalbe Milko Indonesia. Analysis of the data used in the form of descriptive analysis, simple linear regression analysis, hypothesis testing (t test), and the correlation coefficient test (r) and determination (R2). The results of this study indicate that the effectiveness of online training has a positive and significant effect on the performance of employees of the production department of PT Kalbe Milko Indonesia with an effect of 9.4%.